Building a Profession from the Ground Up: A Longitudinal Study of Teacher Professional Development and Pedagogical Innovation in Papuan Private Schools - Iis Sugandhi; Arya Ganendra; Aaliyah El-Hussaini; Gayatri Putri; Evelyn Wang; Anita Havyasari; Muhammad Hasan (Enigma in Education, 2025)
Teacher quality is the most significant school-based determinant of student success, yet fostering professional excellence in remote and culturally diverse regions like Papua, Indonesia, presents profound challenges. Private schools often fill critical educational gaps but their teachers can be professionally isolated. This study addressed the gap in long-term, evidence-based research on teacher professional development (TPD) in this unique context. A three-year (2021-2024) concurrent mixed-methods longitudinal study was conducted. The study involved 50 teachers from a network of five private schools in urban, semi-rural, and remote highland regions of Papua. A comprehensive TPD program, focusing on student-centered learning and culturally responsive pedagogy, was implemented. Quantitative data were collected annually using the Teacher Pedagogical Knowledge Test (TPKT), the Teacher Self-Efficacy Scale (TSES), and a structured Classroom Observation Protocol. Qualitative data were gathered through semi-structured interviews, teacher reflective journals, and focus group discussions with Professional Learning Communities (PLCs). Quantitative data were analyzed using repeated measures ANOVA, while qualitative data were analyzed thematically. The longitudinal quantitative analysis revealed statistically significant improvements across all three years. Mean TPKT scores increased from 48.5 (SD=11.2) at baseline to 79.8 (SD=8.5) at endline (F(2, 98) = 157.2, p <0.001). Teacher self-efficacy scores also showed significant growth (F(2, 98) = 112.9, p <0.001). Classroom observations confirmed a marked shift from teacher-centered to student-centered practices. Qualitative findings identified three core themes: (1) "From Transmission to Facilitation: A Pedagogical Awakening," detailing the shift in teachers' core beliefs about learning; (2) "The Power of the Collective," highlighting the crucial role of PLCs in sustaining motivation and collaborative problem-solving; and (3) "Navigating the Cultural Interface," illustrating the teachers' journey in adapting curriculum to be more culturally responsive. In conclusion, sustained, context-specific, and collaborative TPD can foster profound and lasting improvements in teacher knowledge, self-efficacy, and classroom practice, even in highly challenging environments. The findings advocate for a shift away from isolated, short-term workshops towards integrated, long-term models that prioritize peer collaboration and cultural relevance, revealing a clear pathway from knowledge acquisition to a transformed professional identity.